Building religiusity and independence of life as a means of increasing self efficacy in middlers and beggs - Mujahid; Subiyantoro; Sulistya, Heru (Universitas Islam Malang, 2025)
The crisis of social welfare has shown significant fluctuations each year. According to census data from Bappeda Yogyakarta, the number of PMKS/PPKS in 2019–2020 reached 637,457 individuals. This number sharply decreased by 534,711 to 102,746 individuals in 2021–2022. Such conditions highlight a serious social issue that adds complexity to urban challenges. This study explores the factors behind homelessness and begging, focusing on the context of BRSBKL Yogyakarta. It also aims to strengthen religious, psychological, and life independence aspects of the center’s residents. Using a Participatory Action Research (PAR) approach, the one-month program involved 25 BRSBKL residents and several expert practitioners. The study found that the residents included homeless individuals (both involuntary and by choice), beggars, and former persons with mental disabilities identified by the Social Affairs Office. Religious values were reinforced through mentoring sessions, with six thematic lectures delivered by facilitators. Psychological support was provided through expressive therapy using drawing activities, led by a professional psychologist. Life skills were developed through hands-on training, such as making flower vases with raffia and rattan rope and participating in haircutting workshops. These combined efforts aimed to equip residents with the emotional, spiritual, and practical tools necessary for more independent and dignified living.